Sound matters : essays on the acoustics of modern German culture - Alter, Nora M., 1962-; Koepnick, Lutz P. (Lutz Peter) (Berghahn Books, 2004)
Acknowledgments -- Introduction: Sound Matters / Nora M. Alter and Lutz Koepnick -- PART I: SOUND NATION? -- Chapter 1. Hegemony through Harmony: German Identity, Music, and Enlightenment around 1800 / Nicholas Vazsonyi Chapter 2. Mahler contra Wagner: The Third Symphony and the Political Legacy of Romanticism / Carl Niekerk -- Chapter 3. Conducting Music, Conducting War: Nazi Germany as an Acoustic Experience / Frank Trommler -- PART II: DISSONANT VISIONS -- Chapter 4. The Politics and Sounds of Everyday Life in Kuhle Wampe / Nora M. Alter -- Chapter 5. Sound Money: Aural Strategies in Rolf Thiele's The Girl / Rosemarie Hester Baer -- Chapter 6. The Castrato's Voices: Word and Flesh in Fassbinder's In a Year of Thirteen Moons / Brigitte Peucker PART III: SOUNDS OF SILENCE -- Chapter 7. Benjamin's Silence / Lutz Koepnick -- Chapter 8. Deafening Sound and Troubling Silence in Volker Schloendorff's Die Blechtrommel / Elizabeth C. Hamilton Chapter 9. Silence Is Golden? The Short Fiction of Pieke Biermann / Christopher Jones -- PART IV: TRANSLATING SOUND -- Chapter 10. Broadcasting Wagner: Transmission, Dissemination, Translation / Thomas F. Cohen -- Chapter 11. Sounds Familiar? Nina Simone's Performances of Brecht Weill Songs / Russell A. Berman -- Chapter 12. Roll Over Beethoven! Chuck Berry! Mick Jagger! 1960s Rock, the Myth of Progress, and the Burden of National Identity in West Germany / Richard Langston -- Chapter 13. The Music That Lola Ran To / Caryl Flinn -- PART V: MEMORY, MUSIC, AND THE POSTMODERN -- Chapter 14. "Heiner Muller vertonen": Heiner Goebbels and the Music of Postmodern Memory / David Barnett -- Chapter 15. The Technological Subject: Music, Media, and Memory in Stockhausen's Hymnen / Larson Powell -- Notes on Contributors -- Index.